Prevalence of Fasciolosis and Cystic Echinococcosis in Slaughtered Cattle in Abattoir of Al-Nassiriyah City - Wesam J.Hansh; QasimM.Al-Taher; Muthenna M.T.Alebady (University of Thi-Qar Journal of Science, 2023)
Thepresent study was conducted from January to May 2018 to identify the infection rate of fasciolosis and cystic echinococcosis in cattleslaughtered in the slaughterhouse of Nassiriyah Municipality, Thi-Qar province. During this study, 524 (247 males and 277 females) cattle were submittedfor postmortem inspection. Chi-square is used to analyze the data. The prevalence of fasciolosis in the examined cattle was (7.25%) while the rate of infection with cystic Echinococcosis was (8.40%) with no significant difference.Infection with fasciolosis and cystic echinococcosis was higher infemales than males.The current study showed significant relevance between the sex of cattle andthe prevalence of both fasciolosis and cystic Echinococcosis (P?0.05). The prevalence of fasciolosis and cystic Echinococcosis were significantly affected among the age groups in cattle (P?0.05).